Zinc pimelate as an effective β‐nucleating agent for isotactic polypropylene at elevated pressures and under rapid cooling rates. Issue 3 (11th June 2020) - Qin, Wei; Liu, Kehua; Xin, Zhong; Ling, Hao; Zhou, Shuai; Zhao, Shicheng
Abstract: Along with the pressure and cooling rate, β‐nucleating agents (β‐NAs) can enhance the formation of β‐crystals during the processing of isotactic polypropylene (iPP), controlling both the polymorphic structure and properties of the resulting iPP product. In this study, we found that synthetic zinc pimelate (ZnPA) is a highly active and selective β‐NA, with the relative β‐crystal content ( k β ) reaching 0.99 after its addition to polypropylene at 0.1 wt%. Using high‐pressure differential scanning calorimetry (HP‐DSC) to study the static pressure effect of ZnPA on the nucleation ability of β‐iPP, we found that a N2 atmosphere lowered the crystallization temperature of polypropylene, while a He atmosphere accelerated the crystallization process upon increasing the pressure. Flash‐DSC revealed that a lower cooling rate (<20°C/s) benefited the formation of β‐crystals. This work could reveal the instability of β‐NAs during the commercial application. Abstract : The synthetic zinc pimelate (ZnPA) is a highly active and selective β‐nucleating agent (NA) for isotactic polypropylene (iPP). Along with the pressure and cooling rate, β‐NA can enhance the formation of β‐crystals during the processing of iPP. A lower cooling rate (<20°C/s) is favorable for the formation of β‐crystals.